2019
DOI: 10.1002/nau.24183
|View full text |Cite
|
Sign up to set email alerts
|

Initial report on distribution of β3‐adrenoceptor in the human female urethra

Abstract: Introduction: Past research has demonstrated that the urethral tonus is mainly under sympathetic control. Since 5 years, a beta 3-adrenoceptor (ADRB3) agonist is available in the treatment of overactive bladder syndrome. The presence of ADRB3 within the human urethra has not been demonstrated to date. Presence of ADRB3 in the urethra could influence urethral tonus. The aim of this study is to investigate the presence of ADRB3 in the human female urethra. Material and Methods: We performed anatomical studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Kummeling et al previously reported that β 3 -AR is expressed in the human female urethra. 14 However, the potential roles of β 3 -AR in the urethral function have not been fully explored. Now that selective β 3 agonists are currently available for treatment in patients with OAB, the question regarding whether and how UP is affected by these agents arises.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kummeling et al previously reported that β 3 -AR is expressed in the human female urethra. 14 However, the potential roles of β 3 -AR in the urethral function have not been fully explored. Now that selective β 3 agonists are currently available for treatment in patients with OAB, the question regarding whether and how UP is affected by these agents arises.…”
Section: Discussionmentioning
confidence: 99%
“…Kummeling et al previously reported that β 3 ‐AR is expressed in the human female urethra 14 . However, the potential roles of β 3 ‐AR in the urethral function have not been fully explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations